CHARACTERIZATION AND QUALITY ASSESSMENT OF INDONESIAN COMMERCIAL BIOFERTILIZERS - Edi Husen Husen; R.D.M. Simanungkalit; Rasti Saraswati; Irawan Irawan (Indonesian Agency for Agricultural Research and Development, 2007)
Biofertilizers currently sold in the market are not labeled with a distinct quality standard. As such, farmers may buy low quality biofertilizers, which can reduce their profit and trust on the benefit of biofertilizers. This paper presents the characteristics of various products of commercial biofertilizers as well as farmers’ knowledge and experience on the products. The study was carried out in 2004-2006 by collecting and analyzing data on registered commercial biofertilizers, checking their availability at the market (39 agricultural shops), and interviewing farmers on their knowledge and experience on the use of biofertilizers on various farming systems in Bandung District, West Java (86 respondents) and Semarang District, Central Java (77 respondents). The quality of biofertilizers was tested in the laboratory based on microbial density and its functional (phenotypic) traits. The study showed that amongst various brands of biofertilizers commercialized, 41 brands of them have been officially registered as commercial products. Two brands of other biofertilizers found in agricultural shops were registered as organic or inorganic fertilizers. In general, each biofertilizer contained two or more microbial strains and was claimed to have multiple functions. However, most of them (>90%) were not labeled with expiry date information. Macronutrient contents (NPK) of some microbial carriers were almost equal to those of organic fertilizers. Around 38% of respondents in Bandung knew biofertilizers and less than 10% have ever used them. In Semarang, however, familiarity and personal experience of the respondents were much lower, i.e. 10% and 3%, respectively. About 67% and 50% of agricultural shops in Bandung and Semarang sold biofertilizers, respectively. Laboratory analyses showed that microbial density of five biofertilizers tested was lower than that of product specification, although most of them were positive for N-fixing and P-solubilizing traits. Some microbial strains contained less than 103 cfu based on the dilution level testing. These figures imply the urgent need to improve the existing quality standard system of biofertilizers including its control mechanisms.